2020
DOI: 10.1002/ctm2.112
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gut microbiota mediates berberine‐induced expansion of immuno‐suppressive cells to against alcoholic liver disease

Abstract: Background Berberine is an isoquinoline alkaloid compound derived from many herbs, which has been used extensively to improve liver function. But action mechanism of its hepatoprotection in alcoholic liver disease (ALD) is far from being clear. Aim To investigate the underlying mechanism of berberine's therapeutic effect on ALD associated with gut microbiota‐immune system axis. Method An animal model fed with ethanol that mimics drinking pattern ideally in ALD patients was established. Liver function was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…level. In addition, an important increase in Akkermansia was only observed after berberine intake, in line with other studies showing berberine’s impact on this interesting bacterium [ 45 , 46 , 47 , 49 ]. The limitation is that we cannot exclude that other bacteria than the ones measured have been affected by the dietary treatments and may contribute to the effects demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…level. In addition, an important increase in Akkermansia was only observed after berberine intake, in line with other studies showing berberine’s impact on this interesting bacterium [ 45 , 46 , 47 , 49 ]. The limitation is that we cannot exclude that other bacteria than the ones measured have been affected by the dietary treatments and may contribute to the effects demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Other bacteria belonging to Lachnospiraceae and Desulfovibrionaceae may also decrease upon berberine treatment in diabetic mice [ 45 ]. Furthermore, the abundance of Terrisporobacter and Helicobacter has been shown to increase while that of Pseudoflavonifractor, Mucisirillum, Alistipes, Ruminiclostridium and Lachnoclostridium decreased after berberine treatment in an animal model of alcoholic liver disease, even if A. muciniphila was the one that was most remarkably influenced by berberine administration [ 49 ]. By which mechanisms would berberine intake affect the composition of the gut microbiota?…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was also reported that BBR changes the overall gut microbial composition, mainly by increasing the abundance of Akkermansia muciniphila . Collectively, their results reveal that BBR attenuates ALD by modulating the gut microbiota and immunosuppressive response in ALD [ 115 ].…”
Section: Bioactive Compounds Ameliorate Ald Via Multiple Pathwaysmentioning
confidence: 99%
“…As one of the important compo-nents of the immunosuppressive network, MDSCs have been shown to facilitate tumor formation by blocking the host immune system [6]. Recent studies support the role of MDSCs as essential regulators of chronic inflammatory liver diseases, and MDSCs are expanded in pathological conditions such as malignancy or infection and suppress antitumor immunity [10], and the liver is an important site of MDSC induction for extrahepatic infections and cancer [20][21][22]. The expression of CD33 and CD11b on activated monocytes and macrophages was associated with the disease progression and poor survival of patients [23].…”
Section: Discussionmentioning
confidence: 99%